1995
DOI: 10.1126/science.269.5231.1714
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Domestication of Cereal Crops by Independent Mutations at Corresponding Genetic Loci

Abstract: Independent domestication of sorghum, rice, and maize involved convergent selection for large seeds, reduced disarticulation of the mature inflorescence, and daylength-insensitive flowering. These similar phenotypes are largely determined by a small number of quantitative trait loci (QTLs) that correspond closely in the three taxa. The correspondence of these QTLs transcends 65 million years of reproductive isolation. This finding supports models of quantitative inheritance that invoke relatively few genes, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
343
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 551 publications
(363 citation statements)
references
References 41 publications
17
343
0
3
Order By: Relevance
“…Individual genes contributing to QTL effects have been identified for some developmental traits, revealing a central role for regulatory genes in complex trait variation. QTLs have been isolated using variations of the positional cloning techniques developed for isolating genes with Mendelian effects (Frary et al 2000;Fridman et al 2000;Johanson et al 2000;Yano et al 2000Yano et al , 2001El-Assal et al 2001;Takahashi et al 2001;Liu et al 2002) and/or by testing candidate genes with relevant function that map to QTL regions (Doebley et al 1995;Wang et al 1999;Thornsberry et al 2001). Methods for testing and verification of the isolated genes may include transformation with transgenic constructs, testing for population-level association of gene polymorphisms with phenotype differences , or quantitative complementation testing (Doebley et al 1995;Mackay 2001).…”
Section: Finding the Genesmentioning
confidence: 99%
See 3 more Smart Citations
“…Individual genes contributing to QTL effects have been identified for some developmental traits, revealing a central role for regulatory genes in complex trait variation. QTLs have been isolated using variations of the positional cloning techniques developed for isolating genes with Mendelian effects (Frary et al 2000;Fridman et al 2000;Johanson et al 2000;Yano et al 2000Yano et al , 2001El-Assal et al 2001;Takahashi et al 2001;Liu et al 2002) and/or by testing candidate genes with relevant function that map to QTL regions (Doebley et al 1995;Wang et al 1999;Thornsberry et al 2001). Methods for testing and verification of the isolated genes may include transformation with transgenic constructs, testing for population-level association of gene polymorphisms with phenotype differences , or quantitative complementation testing (Doebley et al 1995;Mackay 2001).…”
Section: Finding the Genesmentioning
confidence: 99%
“…The power to detect specific epistatic interactions is especially limited by multiple testing considerations in QTL experiments because the number of possible two-way interaction terms increases approximately in proportion to the square of the number of main effects. Doebley et al (1995) found that the effects of QTLs for plant architecture differences between maize and teosinte varied depending on the genetic background in which they were evaluated. More recently, Lauter and Doebley (2002) also found genetic variation for some of the same plant architecture QTLs within teosinte when hybrids between two teosinte subspecies were testcrossed to maize.…”
Section: Limitations Of Qtl Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of this evidence suggests that pathways and loci controlling shattering are deeply conserved across taxa, and that homologous mechanisms and loci underlie indehiscence [19,20]. As a consequence, these shared domestication-related loci became common targets of breeding programs.…”
Section: Introductionmentioning
confidence: 99%